PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X IPS3 SMA NEGERI 1 TELUK KUANTAN - Khairani, Putri; Heleni, Susda; Zuhri, Zuhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve the learning process and improve the learning outcomes of students of class X IPS3 SMA Negeri 1 Teluk Kuantan even semester of the academic year 2018/2019. Form of research conducted is action research (PTK) with 2 cycles. The subjects of as many as 35 students, consist of 19 boys students and 16 girls students with heterogeneous ability. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on qualitative analiysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test IIare respectively 12 students (34,2%), 13 students (37,1%) and 20 students (57,1%). Results of this research indicates that application of the Cooperative learning structured approach Numbered Heads Together can improve learning process and increase mathematics learning outcomes from the students at class X IPS3 SMA Negeri 1 Teluk Kuantan even semester academic years 2018/2019.Key Words: Student’s Math Achievement, Cooperative Learning Structural Approach ofNumbered Heads Together, Classroom Action Research.